A Analisis Pengembangan Objek Wisata Danau Tolire Di Kota Ternate: Analisis,Pengembangan,Objek,Wisata,Danau,Tolire,Di,Kota,Ternate - nadira senen; Agus Salim; Rusneni Ruslan (Fakultas Teknik Universitas Bosowa, 2022)
This study aims to analyze the factors that influence thedevelopment of the Tolire Lake tourism object in Ternate City and how theconcept of developing Tolire Lake tourism object in Ternate City is. Thedata obtained were then analyzed using chi-square analysis test and SWOTanalysis. From the results of the chi-square analysis test that has beencarried out, it can be concluded that the factors that influence thedevelopment of Lake Tolire tourism objects are the variables of touristattraction, tourist facilities, tourist infrastructure, information andpromotion and security and comfort. Then from the results of the SWOTanalysis, the concept of developing Lake Tolire tourism objects is obtained,namely combining the concepts of developing natural tourism, culturaltourism, and artificial tourism as the main concept in the development ofTolire Lake tourism objects as regional mainstay tourism, providinginvestment opportunities and facilitating all licensing processes in terms ofdevelopment to attract the attention of the private sector in contributing tothe development of Tolire Lake tourism objects, improving the quality oftourism supporting facilities and infrastructure in order to encouragingregional development and increasing competitiveness and attracting touriststo visit, the need for information and promotion efforts in the development ofLake Tolire attractions through the implementation of local events to cityevents as a promotional medium for the wider community, as well as theneed for community participation in tourism management in order toimprove the home stey of the community and encourage increasedemployment in the tourism sector.